The Impact Of Accounting Digitization And Financial Literacy On The Performance Of Msmes In Pematangsiantar City - Martina, Sri; Ferdila, Ferdila; Damanik, Pandapotan (Jurnal Ilmiah Accusi, 2024)
This study examines the influence of accounting digitalization and financial literacy on the performance of MSMEs in Pematangsiantar City. MSMEs are an important sector in the local economy, but they face challenges in increasing competitiveness, especially related to financial management and technology adoption. Digitization of accounting can improve the efficiency and accuracy of financial data, while financial literacy helps MSME owners make wiser financial decisions. Using quantitative methods and multiple linear regression analysis, the results show that accounting digitization and financial literacy have a significant positive influence on the performance of MSMEs, both partially and simultaneously. A determination coefficient of 0.411 indicates that these two variables explain 41,1% of the variation in MSME performance. These findings support the importance of increasing digital capacity and financial literacy for MSMEs in strengthening competitiveness and sustainability